On the Hermite-hadamard type inequalities for convex functions and convex functions on the co-ordinates in a rectangle from the plane - Hwang, Shiow-Ru (Tamsui Oxford Journal of Mathematical Sciences)
In this paper, we established some inequalities of Hermite-Hadamard type for convex functions and convex functions on the co-ordinates defined in a rectangle from the plane.